2017
DOI: 10.1093/humrep/dew354
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the genetic spectrum ofANOS1mutations in patients with congenital hypogonadotropic hypogonadism

Abstract: N/A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 28 publications
0
21
1
3
Order By: Relevance
“…In our study, we also found some patients in whom HH was combined with hearing impairment, renal agenesis and synkinesis. The sense of smell of 12 patients with KS was inconsistent with MRI analysis of the olfactory bulb, which has been reported previously . Mutations in the genes PROKR2 (17.6%) , FGFR1 (13.7%) , CHD7 (7.8%) and KAL1 (5.9%) were found to be common in the patients of this paediatric study, whereas FGFR1, CHD7, GNRHR and KAL1 were the most common genetic causes in a previous study of adult patients where the proportion each was no more than 10% .…”
Section: Discussioncontrasting
confidence: 85%
“…In our study, we also found some patients in whom HH was combined with hearing impairment, renal agenesis and synkinesis. The sense of smell of 12 patients with KS was inconsistent with MRI analysis of the olfactory bulb, which has been reported previously . Mutations in the genes PROKR2 (17.6%) , FGFR1 (13.7%) , CHD7 (7.8%) and KAL1 (5.9%) were found to be common in the patients of this paediatric study, whereas FGFR1, CHD7, GNRHR and KAL1 were the most common genetic causes in a previous study of adult patients where the proportion each was no more than 10% .…”
Section: Discussioncontrasting
confidence: 85%
“…In familial forms, heterozygous women are always asymptomatic carriers (2,12,(69)(70)(71)(72). However, one series identified 10 women harboring variants.…”
Section: Kal1/anos1mentioning
confidence: 99%
“…Other signs associated with this genetic form, such as mirror movements (also called bimanual synkinesis) and renal agenesis, are frequent, but they do not always cosegregate with the mutation identified in a given family (69,70,(71)(72)(73)(74)(75)(76), for reasons that are still not clear. Other, rarer associated signs such as deafness (35)(36)(37)(38)(69)(70)(71)(72)(73)(74)(75)(76) and vas deferens agenesis, have been described in men with KAL1/ANOS1 mutations (69-74) but their inconsistent presence remains unexplained.…”
Section: Kal1/anos1mentioning
confidence: 99%
See 1 more Smart Citation
“…Patients most often seek medical care with an initial complaint of delayed onset of puberty. Clinical diagnosis is made when delayed puberty presents accompanied by anosmia and after laboratory confirmation of low values of testosterone, luteinizing hormone (LH), and follicle stimulating hormone (FSH) (Gonçalves et al ., ).…”
Section: Introductionmentioning
confidence: 97%